(untitled) (Journal of Economic Research & Business Administration, 2016)
The economic crisis, its causes and consequences are one of the most actively debated topics of the world economy, which is in the center of the attention of politicians, economists, scientists, experts, even among ordinary people. There are different theories, opinions, concepts identified the causes contributing to the economic crisis. Due to the cyclical nature of the market economy system of states faced with the crisis, which must be overcome in order to achieve economic growth of the state. you need to know to overcome the crisis, as well as their causes, consequences and what tools, models should be used. One of the tools for solving the economic problems of the world economy can currently serve the Islamic (ethical) economic system. Islamic model – it is quite dynamic in the world, a young model, which is based on Sharia law. Its prospects are very broad, as well as in foreign countries, as well as all over the world.